The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/23779608221090013
|View full text |Cite
|
Sign up to set email alerts
|

Student Interviews Exploring the Influence of the Coronavirus Pandemic on Graduate Nursing Education

Abstract: Introduction Advanced practice nurses are needed to fill the primary healthcare gap in the United States. Advanced practice/graduate nursing students were profoundly affected by the coronavirus pandemic in ways that may impact their educational experience. Objective The objective of this study was to explore the influence of the coronavirus pandemic on the educational experience of graduate nursing students. Methods An exploratory descriptive qualitative study using semistructured video conferencing interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The majority of students did say they consulted the person they felt was most resourceful, and it seems that family and friends were the people who best fulfilled this need. Similar findings were also supported in other studies by Doolan et al (2020) and Nodine et al (2022) who reported that students are more likely to identify with family and to consult peers who are experiencing the same problems, rather than their educators, whom they prefer to consult for content material.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The majority of students did say they consulted the person they felt was most resourceful, and it seems that family and friends were the people who best fulfilled this need. Similar findings were also supported in other studies by Doolan et al (2020) and Nodine et al (2022) who reported that students are more likely to identify with family and to consult peers who are experiencing the same problems, rather than their educators, whom they prefer to consult for content material.…”
Section: Discussionsupporting
confidence: 88%
“…(2020) and Nodine et al. (2022) who reported that students are more likely to identify with family and to consult peers who are experiencing the same problems, rather than their educators, whom they prefer to consult for content material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies in previous epidemics reported that access to personal protective equipment improved students' desire for voluntary help and care provision to patients [50][51][52]. Moreover, clinical education during the pandemic can be provided in clinical laboratories [53] or vaccination clinics [54]. Tese strategies together with simulated environments, skill laboratories, educational videos, and discussions about clinical cases can be used to improve the quality of clinical education in epidemics.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the decision of the Ministry of Education and Culture, all tertiary institutions, higher education services, and schools are expected to provide online learning. One of the institutions required to implement the directive is nursing education (5,6). Online learning aims to prevent transmission of the COVID-19 virus, which is still very high.…”
Section: Introductionmentioning
confidence: 99%